Anorectal Abscess - Kata, Anna; Abelson, Jonathan S. (Clinics in Colon and Rectal Surgery, 2023)
Anorectal abscesses are a common colorectal emergency. The hallmark of treatment is obtaining source control while avoiding injury to the underlying sphincter complex. Understanding the anatomy of an anorectal abscess is critical to planning the appropriate drainage strategy and decreasing the risk of complex fistula formation. Use of antibiotics should be reserved for those with extensive cellulitis, signs of systemic infection, or patients who are immunocompromised. Whether antibiotics prevent future fistula formation is an area of active research. Primary fistulotomy at time of the index drainage is controversial; however, there may be situations where it is appropriate. It is important to counsel patients that after effective drainage of an anorectal abscess, they have a 30 to 50% chance of developing an anal fistula that will then require further treatment.
Keywords: anorectal abscess; perianal abscess; anal fistula